2021
DOI: 10.1007/s40119-021-00234-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities in Cardiology-Related COVID-19 Publications

Abstract: Introduction: Female authors are underrepresented in cardiology journals, although prior work suggested improvement in reducing disparities over time. Early in the recent COVID-19 pandemic, female authorship continued to lag that of their male counterparts despite a surge in publications. The cumulative impact of the COVID-19 pandemic on authorship gender disparities remains unclear. We aimed to characterize gender disparities in COVID-19-related cardiology publications across the duration of the ongoing pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Studies of fully peer-reviewed accepted and published articles have, to date, been smaller and restricted to specific journals or groups of journals within a particular field. Five of these articles purporting to investigate gender discrepancies in publishing within the pandemic offer no year comparator to relate their data specifically to this time frame ( Bittante et al, 2020 ; Vasti et al, 2021 ; Pinho-Gomes et al, 2020 ; Misra et al, 2021 ; Mazzalai et al, 2022 ). These articles do reinforce the understanding that women publish fewer papers than men across medical research but allow limited interpretation of the impact of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of fully peer-reviewed accepted and published articles have, to date, been smaller and restricted to specific journals or groups of journals within a particular field. Five of these articles purporting to investigate gender discrepancies in publishing within the pandemic offer no year comparator to relate their data specifically to this time frame ( Bittante et al, 2020 ; Vasti et al, 2021 ; Pinho-Gomes et al, 2020 ; Misra et al, 2021 ; Mazzalai et al, 2022 ). These articles do reinforce the understanding that women publish fewer papers than men across medical research but allow limited interpretation of the impact of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 16 bibliometric publications that included an analysis of COVID-19 related papers, 11 reported that men were disproportionately represented as authors of COVID-19 papers. 39,42,46,53,57,58,62,63,67,71,74 There was some variation depending on authorship position; for instance, 2 papers that reported a significant difference in the proportion of women first authors did not report the same effect for last authors. 39,57 For example, Andersen et al 39 compared a sample of 1,893 COVID-19 papers published in medical journals between January and June 2020 with a sample of 85,373 papers published during 2019 in the same journals.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 44 articles selected for extraction, 22 (50%) focused on academic medicine in general rather than on a specific medical area 26,39,43,44,46,50,52–54,56–60,63,68,70,71,75,78–80 ; the remaining publications focused on cardiology (n = 4, 9%), 42,69,72,74 radiology (n = 4, 9%), 61,64,66,73 emergency medicine (n = 2, 5%), 41,55 hematology or transfusion medicine (2, 5%), 40,47 ophthalmology (n = 2, 5%), 48,62 oncology (n = 2, 5%), 45,49 psychiatry (n = 1, 3%), 67 obstetrics and gynecology (n = 1, 3%), 81 osteopathic medicine (n = 1, 3%), 77 pediatrics (n = 1, 3%), 76 surgery (n = 1, 3%), 51 and urology (n = 1, 3%). 65 Articles were divided into 2 broad categories: nonempirical articles that did not collect or analyze primary or secondary data (n = 15, 34%) 26,48–50,54,59,60,68–70,72,73,77,79,80 and empirical articles that collected and/or analyzed data (n = 29; 66%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations